Effects of kinds of alkali-activated ions on geopolymerization process of geopolymer cement pastes. (26th July 2021) - Yuan, Jingkun; Li, Lizhi; He, Peigang; Chen, Zhangwei; Lao, Changshi; Jia, Dechang; Zhou, Yu
Graphical abstract: Highlights: Three geopolymer (MGP) activated by Cs +, K + and Na + were prepared, respectively. Effects caused by alkali-activated ion on geopolymerization process were disclosed. Kinds of alkali metal ions had a decisive influence on geopolymerization process. Geopolymerization process can be obvious accelerated as rising of M' atomic number. Abstract: Three kinds of geopolymer cement pastes (GP) activated by different kinds of alkali-activated ions (Na +, K + and Cs +, respectively) were prepared, and the effects caused by the kinds of alkali-activated ions on geopolymerization process were evaluated. The whole geopolymerization process was divided into reacting stage (Stage I ) and curing stage (Stage II ) successively. The results indicated that the dissolution of raw materials and diffusion process of the ionic groups formed by dissolution were crucial for the Stage I, while Stage II were dominated by polymerization between ionic groups and microstructure reorganization process of geopolymer gel, respectively. The transformed from Al V and Al VI to Al IV throughout whole geopolymerization process, and the transformation rate in Stage II was much higher than that in Stage I . The geopolymerization process was dramatically accelerated with rising of atomic number of alkali-activated ions in corresponding geopolymer cement pastes. The atomic number of alkali metal ion was proportional to the basicity of the system environment. Therefore, as the rising of the atomic number of alkali-activated ions, the geopolymerization reaction process of corresponding geopolymer cement pastes, contained reaction rate and the overall geopolymerization degree, also had been enhanced simultaneously.